Art herstory and my interrupted bath. (30th December 2022) - Lightman, Sarah
A visual conversation through art herstory and mothering, made during the first lockdown of 2020. Faced with a lack of private space, the author locks herself in the bath and discusses paintings from the past as she grapples to make art when her son wants her full attention.